Konsep Kepemimpinan Tuhan Yesus - Sunardi, Agus (Sekolah Tinggi Teologi Borneo, 2021)
Abstract: Leadership becomes an issue or very interesting conversation to talk about. Various kinds of ideas that arise try to discuss and solve problems that are developing. One idea to discuss the issue of Leadership in general is discussed in various sources of books that are being circulated written by leadership figures both in Indonesia and from abroad. And the ideas suggested by them are good enough to help in knowing the problems that are developing. Involving discussions that were interesting to discuss, it turned out that the Apostles Paul, Peter, and Prophet Moses had also taken an important role in this warm discussion about leadership. Each of them has strong enough arguments to answer leadership problems according to the standards of inspired truths through the power of the Holy Spirit. Discussing further about some theologists agree on Jesus Christ as a figure of centralization in spiritual leadership. The texts that will be discussed in explaining some very important things about students as the forerunner of a spiritual leader will one day lead, have an ambition to be who is the greatest in the kingdom of God. The ambition or desire is so strong that it needs to involve the great teacher in helping the debate. So that this debate becomes an interesting issue in the Gospel of Matthew and needs to be written through the inspiration of the Holy Spirit so that readers are expected to understand the problem of leadership. The relevance of Jesus Christ's words about leadership will be very useful for us in the present and also still in future.Keywords: Jesus Christ; leadership; theologicalAbstrak: Kepemimpinan menjadi isu atau pembicaraan yang sangat menarik untuk dibicarakan. Berbagai macam ide yang muncul berusaha untuk membahas dan memecahkan masalah yang sedang berkembang. Salah satu ide untuk membahas masalah kepemimpinan secara umum tersebut dibahas dalam berbagai macam sumber buku yang sedang beredar ditulis oleh tokoh kepemimpinan baik di Indonesia maupun dari manca negara. Dan gagasan-gagasan yang disarankan oleh mereka cukup baik untuk menolong dalam mengetahui permasalahan yang sedang berkembang. Melibatkan diskusi yang sedang menarik dibicarakan, ternyata Rasul Paulus, Petrus, dan Nabi Musa juga telah ikut mengambil peranan penting dalam pembahasan yang hangat tentang kepemimpinan ini. Masing- masing dari mereka telah memiliki argumentasi yang cukup kuat menjawab problema kepemimpinan menurut standar dari kebenaran yang telah diinspirasi melalui kuasa Roh Kudus. Mendiskusikan kepemimpinan lebih lanjut beberapa ahli theologi sepakat Yesus Kristus sebagai tokoh sentralisasi dalam kepemimpinan rohani. Teks-teks yang akan dibahas dalam menjelaskan beberapa hal yang sangat penting tentang murid-murid sebagai cikal bakal pemimpin rohani suatu saat akan memimpin, telah memiliki sebuah ambisi untuk menjadi siapakah yang terbesar dalam kerajaan Allah. Ambisi atau keinginan itu begitu kuat sehingga perlu melibatkan sang guru Agung dalam menolong perdebatan. Akibatnya perdebatan ini menjadi isu yang menarik dalam Injil Matius dan perlu ditulis melalui ilham Roh Kudus agar para pembaca diharapkan dapat mengerti tentang masalah kepemimpinan tersebut. Relevansi dari perkataan Yesus Kristus tentang kepemimpinan itu akan sangat bergruna bagi kita di masa sekarang dan juga masih berlaku di masa yang akan datang.Kata kunci: kepemimpinan; teologis; Tuhan Yesus